From Double-Dip Recession to Fragile Recovery - World Bank (Washington, DC, 2014)
After the double-dip recession, as a group the six South East European countries (SEE6)- Albania, Bosnia and Herzegovina, Kosovo, FYR Macedonia, Montenegro, and Serbia-are now making a fragile recovery. Last year the recession in the Eurozone had adverse impact on external demand and Foreign Direct Investment (FDI) in SEE6 and the severe winter and a summer drought crippled agriculture and affected trade, energy, and economic activity overall. However, the recovery in SEE6 is still tentative. In some countries nonperforming loans, sluggish credit recovery, continued deleveraging, and fiscal consolidation are exerting a drag and recovery in SEE6 is unlikely to accelerate as long as the Eurozone remains in recession. The SEE6 region is projected to grow 1.7 percent in 2013, signaling the end of the 2012 double-dip recession. Even though growth will in general be fragile, it will be on the upswing in all six countries. Kosovo again is expected to have the highest growth (3.1 percent), thanks to major public investments and a significant inflow of remittances. Against the backdrop of this tentative and fragile recovery, SEE6 countries should, as argued in the last report, intensify their efforts to reform structural areas. Fiscal consolidation efforts should become easier now that the output and revenue outlook is improving. The investment climate needs to be improved substantially, especially in the main areas of weaknesses: construction permits and licenses, barriers to entrepreneurship, and skills and infrastructure. One of the main worries in this nascent recovery is that SEE6 economies are plagued by high unemployment, especially youth unemployment, and they are not creating jobs fast enough to absorb new entrants into the labor force. Emigration continues as the current environment for doing business exacerbates the difficult labor market conditions.